Update on Persistent Excessive Daytime Sleepiness in OSA - Javaheri, Sogol; Javaheri, Shahrokh (Chest, 2020)
OSA is a highly prevalent sleep disorder, and subjective excessive daytime sleepiness (EDS) is the cardinal symptom for which many individuals seek medical advice. Positive airway pressure (PAP) devices, first-line treatment for OSA, eliminates EDS in most patients. However, a subset of patients suffers from persistent EDS despite adherence to therapy. Multiple conditions, some reversible, could account for the residual sleepiness and need to be explored, requiring detailed history, review of PAP data from the smart card, and sometimes additional testing. When all known causes of EDS are excluded, in adequately treated subjects, the purported mechanisms could relate to long-term exposure to the OSA-related sleep fragmentation, sleep deprivation, and hypoxic injury to the arousal system, shifts in melatonin secretion, or altered microbiome. Independent of the mechanism, in well-treated OSA, pharmacological therapy with approved drugs can be considered. Modafinil is commonly prescribed to combat residual EDS, but more recently two drugs, solriamfetol, a dual dopamine-norepinephrine reuptake inhibitor, and pitolisant, a histamine H3 receptor inverse agonist, were approved for EDS. Solriamfetol has undergone randomized controlled trials for treatment of EDS associated with both OSA and narcolepsy, exhibiting robust efficacy. Solriamfetol is renally excreted, with no known drug interactions. Pitolisant, which is nonscheduled, has undergone multiple RCTs in narcolepsy, showing improvement in subjective and objective EDS and one OSA trial showing improvement in subjective EDS.